Mass Transfer of U(IV) in HCl-TBP System Employing Free Falling Single Drop Technique in Different Diluents - Jassim, T N (Al-Nahrain Journal of Science, 2013)
In this work free falling drop technique has been utilized to study the mass transfer kinetics of U(IV) in 30% TBP–HCl system using different diluents, namely kerosene, toluene and (LAB+BTX) which is a mixture of equal volumes of linear alkyl benzene (LAB), and isotropic mixture of benzene, toluene and xylene (BTX). The concentrations of hydrochloric acid and U(IV) in the aqueous phase were 3.4-7.2 M and 1M, respectively. It was found that the kinetic rates increased with increasing the aqueous hydrochloric acid concentration and drop diameters. Furthermore, the results revealed an increase in the activation energy (Ea) according to the diluent’s nature and followed the sequence, (LAB + BTX) < toluene < kerosene. Also the physical properties of the diluents influenced the rate constant of U(IV) extraction, which increased in the order : kerosene < toluene < ( LAB+BTX) .